Global convergence via descent modified three-term conjugate gradient projection algorithm with applications to signal recovery - Abubakar, Auwal Bala; Kumam, Poom; Awwal, Aliyu Muhammed (Results in applied mathematics, 2019)
In this article, we propose a three-term conjugate gradient projection algorithm for solving constrained monotone nonlinear equations. The global convergence of the algorithm was established under suitable assumptions. Numerical examples presented indicate that the algorithm has a very good performance in solving monotone nonlinear equations. Finally, the algorithm is applied to solve signal recovery problems.